Photocatalysis: Quantum‐Sized Metal Catalysts for Hot‐Electron‐Driven Chemical Transformation (Adv. Mater. 48/2018). Issue 48 (26th November 2018) - Wei, Qilin; Wu, Siyu; Sun, Yugang
Abstract : In article number1802082, Yugang Sun and co‐workers highlight the efficient generation of hot electrons in quantum‐sized metal nanoparticles upon photo‐illumination. The hot electrons can be injected into the chemical bonds of the adsorbate molecules to activate the adsorbates followed by chemical transformation, resulting in the production of valuable chemicals.